EU trade policy reform: towards reciprocal concessions with developing countries - Arevik Gnutzmann-Mkrtchyan; Maximilian Volmer (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2022)
The European Union (EU) supports developing countries with a unilateral trade preference scheme. The scheme underwent a major reform in 2014, in which many countries lost access to reduced tariff rates. We analyse how this radical step that removed preferences from 103 countries by 2018 fits into the EU's strategy to promote bilateral agreements and how it affected imports from the removed beneficiaries. Using the gravity model of trade with high-dimensional fixed effects, we show that the removal results in a significant decline in exports of affected developing countries. Some countries formed a bilateral free trade agreement with the EU, in which case the negative effect of removal of unilateral trade preferences is compensated but we do not find significant and consistent additional benefits. Thus, the threat of removal can be seen as a lever for beneficiaries that are about to become ineligible to negotiate a bilateral agreement with the EU.
Keywords: F13; F14; O19; O24; D78; 330; trade preferences; reciprocity; GSP; FTA; gravity model